Differential scattering cross section of the dense semiclassical plasma based on the Born method - Shalenov, E.O.; Kossymkyzy, Zh.; Seisembayeva, M.; Masheyeva, R.; Jumagulov, M.N.; Dzhumagulova, K.N. (Recent Contributions to Physics, 2020)
In this work the results of investigation of collisional properties of the dense semiclassical plasma on the basis of the effective interaction potentials are presented. Interaction models take into account the quantum- mechanical effects of diffraction and the effect of dynamic screening. It is shown that dynamic charge screening increases the phase shifts and the scattering cross sections in comparison with static one. The study of the properties of the dense semiclassical plasma is difficult, firstly, because of the inadequacy of the choice of particle interaction models and, secondly, the imperfection of the existing theoretical methods to study the properties of such complex systems. Collisional processes determine practically all properties of the plasma, its composition, thermodynamics, transport characteristics, electrodynamic properties, etc. Therefore, it is especially important to be able to conduct research correctly and reliably at the level of elementary processes. Traditionally, the study of elementary processes within a particular model begins with obtaining cross sections for elastic scattering, with the first estimates can and should be carried out on the basis of simple methods, to which the Born method applies. The collision cross sections directly depend on the relative velocity of the colliding particles, it sits in the equations themselves, which allow the cross section to be calculated, but in most cases the interaction potential does not take into account this velocity. Such formulation is not entirely correct and more consistent is the use of the dynamic potential of the interaction of particles in the study of their collisions. It was found that at the scattering angle that is close to zero the differential cross section has a finite value which depends on the wave vector of the incident particle (its energy), while the model with static screening does not show it. Conclusions were maid.